AApplication Of Dietary Approaches To Stop Hypertension (Dash) Diet: An Effort To Lower Blood Pressure In Individuals With Hypertension - Nata Ratnawati; Lina Andriani; Susanti Susanti; Difran Nobel Bistara (UNUSA Press, 2021)
Diet DASH (Dietary Approaches To Stop Hypertension) is one way to reduce hypertension. Dietary factors (dietary compliance) are important things to consider in patients with hypertension. Patients with hypertension should adhere to the DASH diet in order to prevent further complications. The implementation method in the community service program is by providing health education about the DASH diet management application in the form of lectures and questions and answers. The participants of this activity were residents of the Brigadier General Katamso area RT 23 RW 05 Waru Sidoarjo. The results of blood pressure showed that after being given KKL activities in the form of counseling, blood pressure checks, from a total of 10 residents (100%) who participated in KKL activities in the Brigadier General Katamso 2 RT 23 RW 05 Kelurahan Kedung Rejo, Waru District, the results of blood pressure for most residents in the area of ​​Brigjen Katamso 2 RT 23 RW 05 Kedung Rejo Village Waru District before the KKL activity in the category 1 hypertension category was 6 people (60%), and after the KKL activity was in the high normal category there were 5 people (50%). Based on these data, it can be seen by using the Wilcoxon Signed Rank Test statistical test, the knowledge value p value = 0.003 so there is an effect of DASH diet counseling on blood pressure. Most of the respondents (50%) have a consumption pattern that triggers hypertension is not good at the time of the pretest. After being given the intervention and doing a posttest, it showed that most of the respondents (90%) had a good consumption pattern that triggers hypertension. This means that there is a decrease in consumption patterns that trigger hypertension before and after being given the DASH diet information guidebook for hypertension patients. The existence of a significant difference in knowledge between before and after being given the DASH dietary information guidebook for hypertension patients identified that health education about DASH diet information could increase public knowledge. Knowledge of hypertension patients increased after being given health education using the DASH diet manual. This increase in knowledge allows people to adjust their eating patterns as recommended in the DASH diet guide book